A garganta da terra: música, memória e conflito agrário nos montes de Maria (Colômbia) (1960-2000) - Díaz, Jaili Ivinai Buelvas (2019)
This dissertation analyzes the struggles for land in the Montes de Maria region in northern Colombia, from the agricultural production of its inhabitants. The struggle for land in this region reached its peak since the year 1960 with the founding of the Asociación Nacional de Usuarios Campesinos - ANUC [National Association of Peasant Users], which quickly turned against the State due to the disadvantage conditions identified by the peasants and the corresponding actions that they carried out to demand their rights to the State and landowners. From this struggle, the region faced an armed confrontation, with its maximum peak in the 80s and 90s. Parallel to the political organization, this dissertation argues that the cultural production of the residents had particularities associated with their worldview that allows us to understand much better this political process. Thus, the music of gaitas appears as a tool for analyzing the social situation, as an expression of local identity and thought in the region and as a mediator of the political. The music-body-land relationship, inscribed in the musical practice, allows us to understand the complicated social situation and manifests the objectives of the struggle for the land as a struggle for the possibility of cultural existence of the montemarian campesinosgaiteros in the last four decades of the twentieth century. For this, we analyze oral sources and documents associated with agricultural production and the struggles for land in the region.